Predictors of vitamin D deficiency and quality of life in obese patients with obstructive sleep apnea - Loh, Huai Heng; Tay, Siow Phing; Koa, Ai Jiun; Yong, Mei Ching; Asri, Said; Chai, Chee Shee; Natasya Marliana, Abdul Malik; Anselm, Su Ting; Bonnie Bao Chee, Tang; Florence Tan, Hui Sieng; Norlela, Sukor (Springer Nature Limited, 2026)
Obstructive sleep apnea (OSA) and obesity are risk factors for adverse cardiovascular outcomes. Vitamin D deficiency (VDD) is linked to metabolic dysfunctions, contributing to cardiovascular disease. In this cross-sectional study, we aimed to determine the vitamin D profile, evaluate the impact of vitamin D level on quality of life (QoL), and identify factors associated with hypovitaminosis D in obese patients with OSA. Anthropometric data, QoL scores, and blood for serum 25-hydroxyvitamin D [25(OH)D] and metabolic parameters were collected from patients who fulfilled study criteria. There was a high prevalence of VDD and insufficiency in the study cohort, but no difference in serum 25(OH)D level across the OSA categories. Serum 25(OH)D level was associated with gender, education status, body mass index (BMI), and triglyceride level. QoL scores were not different across the vitamin D categories but were lower in severe OSA compared to mild and moderate disease. This is the first study reporting factors associated with hypovitaminosis D among OSA patients in a Southeast Asian country and its effect on their QoL. Those with VDD were more likely to be females, have received higher education, with higher BMI and triglyceride levels. The OSA severity and QoL of these patients were not affected by vitamin D levels.